Peningkatan keterampilan dan pengetahuan berbicara dan percakapan Bahasa Inggris Siswa/Siswi SMP Negeri 29 Makassar - Ryan Rayhana Sofyan; Nurfitri Nurfitri (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The partner of this Community Partnership Program (PKM) was SMP Negeri 29 Makassar. The problems are: (1) the lack of vocabulary mastery, (2) the lack of English speaking skills, (3) lack of student confidence in speaking English, and (4) lack of fluency in speaking in English . External targets are English vocabularies and their meanings in accordance with student learning outcomes. The method used is: lectures, demonstrations, discussions, questions and answers, and counterpart partners. The results achieved are (1) partners have knowledge about vocabulary in English, (2) partners have English speaking skills, (3) partners have confidence in learning and developing English speaking skills.